Reservoir Quality of Ngrayong Sandstone in Tempuran Village Area, Rembang Zone, Western part of North East Java Island, Indonesia - Htun, Myo Min (AUN/SEED-Net - JICA, 2017)
The early Middle Miocene Ngrayong Formation is famous reservoir in north-east Java, mainly composed of very loose clean sandstone. The study area is situated near Tempuran Village, Rembang Zone, and that area is still need to confirm the reservoir quality. Ngrayong sandstones are well exposed along the southern flank of Pakel Anticline with east-west trending direction. Seven samples from four different facies from five outcrops conducted for petrophysical (porosity & permeability) and granulometry analysis (grain size & sorting) .The highlight of this research is to determine the reservoir quality of Ngrayong sandstone. Ngrayong Formation consists of laminated to thin bedded sandstone facies (facies 1), thick bedded to massive sandstone facies (facies 2), calcareous sandstone facies (facies 3) and cross bedded sandstone facies (facies 4). According to results of each analysis, facies 1 is very fine to fine grained, well sorted to very well sorted sandstone and, it has porosity (23 to 29.28%) and permeability (725.9 to 2088.03mD). Facies 2 is very fine grained, moderately well sorted sandstone and it possesses porosity (16.26 to 21.25%) and permeability (303.487 to 705.213mD). Facies 3 is fine grained, moderately well sorted sandstone and it has porosity (21.26%) and permeability (263.813mD). Facies 4 is fine grained, very well sorted sandstone and it has porosity (27.58%) and permeability (747.299mD). Base on the overall results of analyzed samples, Ngrayong sandstone have good to excellent porosity and excellent permeability, thus study area can be characterized as a potential reservoir. Keywords: Granulometry; Petrophysic;Ngrayong sandstone; Reservoir; Tempuran Area